Post Junctional Sudomotor and Cutaneous Vascular Responses in Noninjured Skin Following Heat Acclimation in Burn Survivors - Pearson, James; Ganio, Matthew S; Schlader, Zachary J; Lucas, Rebekah A I; Gagnon, Daniel; Rivas, Eric; Davis, Scott L; Kowalske, Karen J; Crandall, Craig G (Journal of burn care & research, 2017)
Thermal tolerance is improved in burn survivors following 7 days of exercise heat acclimation. It is unknown whether post junctional sudomotor and/or cutaneous vascular adaptations in noninjured skin contribute to this improvement. Thirty-three burn survivors were stratified into moderately (17-40% BSA grafted, n = 19) and highly (>40% BSA grafted, n = 14) skin-grafted groups. Nine nonburned subjects served as controls. All subjects underwent a 7-day heat acclimation protocol, which improved thermal tolerance in all groups. Before and after this heat acclimation protocol, post junctional cutaneous vascular responses were assessed by administering increasing doses of sodium nitroprusside (SNP) and methacholine (MCh) using intradermal microdialysis in noninjured skin. MCh infusion was also used to assess post junctional responses in sudomotor function in noninjured skin. Cutaneous vascular responses to SNP and MCh were not different between pre- and post heat acclimation in either group of burn survivors (both P > .05). The maximal sweating rate to MCh increased post acclimation in the control group (0.41 ± 0.20 to 0.54 ± 0.21 mg·min·cm; P = .016) but was unchanged in both groups of burn survivors (both P > .05). The number of sweat glands activated during the highest dose of MCh was elevated in the >40% BSA-grafted group (49 ± 16 to 56 ± 18 glands·cm; P = .005) but was unchanged in control subjects and the <40% BSA-grafted group (both P > .05). Given that post junctional administration of MCh and SNP did not alter sweating or skin blood flow from noninjured skin of burn survivors, improved thermal tolerance in these individuals following heat acclimation is more likely a result of either an increased sweating efficiency or an increased neural drive for sweating.